The Influence Of Work Environment And Compensation On Employee Performance Through Work Motivation (Case Study At PT. Mandiri Press Indonesia) - Atiqul Umam; Retno Purwani Setyaningrum (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of the work environment and compensation on employee performance through work motivation as a mediating variable at PT. Mandiri Press Indonesia. The research uses a quantitative approach with a descriptive method. The population consists of 200 employees at PT. Mandiri Press Indonesia. The sample consisted of 134 respondents selected using cluster sampling. Data were analyzed using SmartPLS 3.0 software. The results indicate that the work environment significantly affects employee performance, both directly and indirectly through work motivation. Compensation does not directly influence performance but has a significant indirect effect through motivation. Motivation is proven to be a strong mediating variable in enhancing employee performance. These findings highlight the importance of creating a supportive work environment and a fair compensation system to improve employee motivation and performance.